OPTIMALISASI SUMBER DAYA DAN PENGUATAN DIGITALISASI DESA BELUMBANG - I Nyoman Agus Suarya Putra; Ni Wayan Wardani; Putu Satria Udyana Putra (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
The Community Service Program will be implemented for approximately three months, from March 2025 to June 2025, in Belumbang Village, Kerambitan District, Tabanan Regency, Bali. This program is driven by the challenges faced by villages in optimizing information technology for data collection, news input on the Village Information System (SID), and digital promotion due to limited human resource knowledge. The main goal is to help village officials digitize Belumbang Village and develop students' soft skills. This method involves situation analysis, preparation (surveys, permits, material preparation), and the implementation of nine main programs, including managing the OPEN SID website, creating village introduction videos, optimizing posyandu and elderly data, and digital literacy training for students. The results show that this activity facilitates data management, introduces the village digitally, raises public awareness about organic waste management, and improves the digital skills of village staff and students. In conclusion, this Community Service Program successfully contributed to digital transformation and community development in Belumbang Village.